Assessment of Eutrophication Status Based on Sub-Surface Oxygen Conditions in the Gulf of Finland (Baltic Sea) - Stoicescu, Stella-Theresa; Lips, Urmas; Liblik, Taavi (Frontiers in Marine Science, 2019)
Sub-halocline oxygen conditions in the deep Baltic Sea basins depend on natural forcing and anthropogenic impact. HELCOM has a long tradition of characterizing the status of the seabed and deep waters by estimating the extent of anoxic and hypoxic bottoms. A eutrophication-related indicator ‘oxygen debt’ has been used in the recent HELCOM assessments and a more sophisticated ‘oxygen consumption’ indicator has been introduced. We describe the oxygen conditions in the Gulf of Finland (GoF) in 2016-2017 based on observations at the Keri profiling station where vertical profiles of temperature, salinity and oxygen were acquired up to 8 times a day. The main aim of the study is to test the applicability of high-frequency data from this fixed automated station and the three adapted oxygen indicators for the eutrophication-related status assessments. The results show that the GoF bottom area affected by hypoxia varied in large ranges from 900 to 7800 km2 with a seasonal maximum in autumn (> 25% of bottoms were hypoxic in autumn 2016). Oxygen debt is the simplest indicator, and the assessment results are less influenced by the wind-induced changes in hydrographic conditions. We suggest that oxygen debt should be assessed just below the halocline and based on data from the stratified season only since, in the GoF, the halocline could be destroyed in winter. For the ‘oxygen consumption’ indicator, a rough oxygen budget, where the contributions of advection and mixing are included, was formulated. Average seasonal consumption values of 0.82 and 0.31 mg l-1 month-1 were estimated in the 50-60 m water layer of the GoF in 2016 and 2017, respectively. The found large difference in consumption values between 2016 and 2017 could partly be related to the uncertainties of advection estimates. We concluded that all three indicators have their advantages and methodological challenges. To increase the confidence of eutrophication assessments both high-frequency profiling should be implemented in the monitoring programs and more accurate estimates of changes due to physical processes are required.